Protein, iron, zinc and calcium concentrations of potatoes following traditional processing as “chuño” - Burgos, G.; Haan, Stef de; Salas, E.; Bonierbale, Merideth W. (Elsevier, 2009)
Samples from unprocessed and processed cooked tubers of the nine most abundant potato cultivars used to prepare the traditional freeze-dried food product, “chuño” in the central highlands of Peru were prepared and analyzed for their protein and mineral concentrations. The protein, iron, zinc and calcium concentration of cooked chuño of the nine cultivars evaluated ranged from 0.49 to 1.15 g, from 0.29 to 0.65 mg, from 0.04 to 0.14 mg and from 18.9 to 31.0 mg per 100 g on a fresh weight basis, respectively. Potatoes processed as chuño have a lower concentration of protein and zinc than unprocessed tubers, and a higher content of calcium, while iron concentration may be expected not to be subjected to changes. Water used in preparing the chuño is suggested to be the cause for an increased calcium concentration in the final product, as the water used had higher calcium content before (1.35 mequiv./l) than after (0.84 mequiv./l) use in the preparation. Thus, water seems to be source of the increased calcium concentration.